Mitigation of greenhouse gas emissions and enhancement of water quality in constructed wetlands: A case study in cold temperate regions of China - Baiyang, Jiang; Yue, Yang; Doh, Shu Ing; Suryati, Sulaiman; Abdul Syukor, Abd Razak (Semarak Ilmu Publishing, 2024)
Constructed wetlands (CWs) have emerged as a green solution for wastewater treatment in many regions. However, their efficacy can be impacted by temperature fluctuations, and the potential emission of greenhouse gases may offset their environmental and ecological benefits. This study focuses on the effluent of one wastewater treatment plant in the cold temperate zone of northern China. It investigates the supplemental treatment effects of CWs on effluents from conventional sewage treatment plants using three plant species: Phragmites australis, Scirpus validus, and Typha orientalisfor phytoremediation. Under 15°C, CWs showed moderate removal efficiencies for COD (35.71-40.28%) and TN (28.79-33.59%), with relatively low CO2 emission flux (43.56-176.56 mg/m2/h) and global warming potential (GWP,2.815- 6.613 mg/m2/h). Among the plants, Scirpus validus demonstrated superior pollutant removal and lower greenhouse gas (GHG) emissions, making it a prime candidate for future use. Additionally, it explores the incorporation of biochar into CW substrates to simultaneously enhance water quality (+9.99% for COD and +22.13% for TN) and mitigate GHG emissions (-9%). The conclusions provide insights into the potential of CWs as complementary measures for conventional wastewater treatment, particularly in reducing GHG emissions and improving water quality in cold temperate regions. These findings contribute to understanding sustainable wastewater management practices in environmentally sensitive areas.